FABRICATION OF PCL-COLLAGEN NANOFIBER USING CHLOROFORM-FORMIC ACID SOLUTION AND ITS APPLICATION AS WOUND DRESSING CANDIDATE - armeda, tri prasetyo (Stem Cell Research and Development Center, Universitas Airlangga, 2017)
In this study, polycaprolactone-collagen nanofiber was prepared with 10% w/v composition using a mixture of chloroform-formic acid. PCL was dissolved in chloroform while collagen was dissolved in formic acid. This research carried out optimization of electrospinning parameters such as flow rate, running time, and collector type to obtain optimum and suitable nanofiber to be applied as wound dressing. The most optimum nanofiber is made with flow rate 0.01 Î¼L/h, running time is 3 hours, and using cylinder collector type. Characterization was performed for five different types of PCL-collagen nanofiber with different treatment, which nanofiber made with cylinder collector, plate collector, addition ofcitric acid, heating treatment, and nanofiber without the addition of collagen. PCL-collagen nanofiber produces smaller diameter about 200 - 600 nm. Based on the test of mechanical properties, addition of collagen causes its mechanical properties to be lower when compared to addition of crosslinking agents by heating or citric acid. The cytotoxicity test was carried out for PCL, PCL-collagen withaddition of citric acid, and PCL-collagen nanofiber treated by heating. PCL was chosen to compare the effect of collagen addition onnanofiber against cell viability. Collagen has an important role for growth, proliferation, and differentiation of cells in tissue engineering. PCL-collagen nanofiber which treated by heating provides better viability of 83.09% while compared to nanofiber with addition of citric acid, because citric acid acidic properties causing the environment around nanofiber have an extreme pH, it may affect the growth of cells and reduce its viability.Keywords:Nanofiber, PCL, collagen, electrospinning, wound dressing, MTT Assay